A1_3 Can the Northern Lights be seen in Leicester - Gosling, Jennifer; Evans, Tamsyn; Keen, Gemma; Evans, Laura (Physics Special Topics, 2009)
The Earth’s auroras are caused by the interaction between the Earth’s magnetosphere and the solar wind.Â This report discusses this mechanism and investigates the conditions that would allow the aurora to be seen at the latitude of the University of Leicester.